Myopic optic disc changes and its role in glaucoma. Issue 2 (March 2019) - Tan, Nicholas Y.Q.; Sng, Chelvin C.A.; Ang, Marcus
Abstract : Purpose of review: Optic nerve head (ONH) changes such as tilt and torsion are associated with the progression of myopia, and may in turn predispose toward glaucoma. At the same time, these ONH deformations also make the structural assessment for glaucoma difficult. Here, we review the mechanisms and changes to the myopic optic disc, and the advances in structural imaging to better evaluate the ONH in myopia. Recent findings: The distance, depth, and angle between the optic disc and the deepest point of the elongated eyeball may be related to the degree and direction of optic disc tilt and torsion. It is hypothesized that as the eyeball grows axially, the disc is pulled toward its most protruded point. These ONH deformations in myopia are thought to induce strain on the lamina cribrosa and the axons passing through it. Recent studies have shown unique characteristics of the lamina cribrosa in myopia that may account for susceptibility toward glaucoma. New developments in imaging the ONH in myopia, including the use of optical coherence tomography-angiography may also further our understanding of the relationship between myopia and glaucoma. Summary: Optic disc changes in myopia are secondary to the configuration of the posterior globe. These ONH deformations may predispose toward glaucoma, although the causative relationship between myopia and glaucoma remains to be further clarified.